Analysis of service quality towards repeater guest satisfaction at The Samaya Seminyak - Ika Fitri Kurnia Sari; I Gusti Agung Bagus Mataram; Dewa Made Suria Antara; Ni Gusti Nyoman Suci Murni (International Journal of Green Tourism Research and Applications, 2021)
The purpose of this study was to determine how satisfied the repeater guest were with the performance of The Samaya Seminyak and to know indicators that had to be improved in order to increase the satisfaction of the repeater guest. The method used is Servqual Test and Important Performance Analysis as the tools to measure repeater guest satisfaction on the existing performance of The Samaya Seminyak. Data were collected from 75 questionnaires repeater guest. Measurement of repeater guest satisfaction was using the theory of 5 dimensions of service quality those are tangible, reliability, responsiveness, assurance, and empathy. The quality of service available at The Samaya Seminyak was unable to meet the quality of service desired by repeater guest. Analysis of service quality is resolved by Servqual test, where 10 out of 15 indicators produce negative gaps, and 5 indicators produce positive gaps. The services that need to be improved in order to increase the satisfaction of repeater guest are indicators of the accuracy and speed of the host and butler staff in providing services appropriately, the ability in providing services to the guests, the ability of the host and butler staff in understanding guests’ wishes quickly, host and butler staff initiative in providing assistance, and host and butler staff knowledge about the products offered.